The Renal Toxicity of Welding Fumes in Heavy Equipment Manufacturer Workers - Mulyana, Mulyana; Adi, Nuri P.; Kurniawidjaja, Meily Kurniawidjaja; Pratami, Vani N.; Wijaya, Andi; Yusuf, Irawan (Indonesian Journal of Clinical Pharmacy, 2015)
Exposure to welding fumes in the workplace has been associated with decreasing renal function. We studied renal function parameters in men workers from heavy equipment manufacturer exposed to welding fumes. This study aimed to evaluate renal function status among worker exposed to welding fumes. A case-control design, random study, was conducted among welder (35 subjects) and nonwelder (35 subjects) with more than 1 years experience in the same job task in a heavy equipment manufacturer. All subjects were completed physical examination, informed consent, questionnaire and laboratory tests. Renal function was easured as creatinine serum using enzimatic method. Urinary heavy metals level was analyzed using inductively coupled plasma mass spectrometry. Comparisson analysis between group was performed to determined median level for each variable. Linear regressionmodel was developed to predict renal function function parameter status urinary heavy metals level as variable. This study showed there were higher creatinine serum, chromium, iron, manganese and nickel in welder than non welder(p<0.05). After multivariate analysis, urinary nickel is a predictor for renal function status among welder. Exposure to welding fumes was significantly correlated with renal function status in welder. Nickel is the predictive variable for renal function. Although statistically significant but in clinical field needs carefully interpreting data.Keyword: Nickel, renal function, welder, welding fumesToksisitas Renal Uap Las pada Pekerja Industri Alat BeratPajanan uap las di tempat kerja telah dihubungkan dengan penurunan fungsi ginjal. Dalam penelitian ini, kami menguji status fungsi ginjal pada pekerja pria yang terpajan uap las di industri alat berat. Penelitian ini mengevaluasi status fungsi ginjal pada pekerja terpajan uap las, dengan desain kontrol kasus, acak, dilakukan pada 35 subjek pengelas dan 35 bukan pengelas yang telah bekerja paling tidak 1 tahun dengan jenis pekerjaan yang sama di industri alat berat. Seluruh subjek telah melakukan pemeriksaan fisik,pengisian form kesediaan setelah penjelasan, kuesioner, dan pemeriksaan laboratorium. Pemeriksaan kadar kreatinin dilakukan dengan metode enzimatik. Pemeriksaan kadar logam berat dalam urin dengan inductively copled plasma mass spectrometry. Dilakukan analisis perbandingan untuk membedakan nilai median antar kelompok. Dilakukan juga analisis multivariat untuk menentukan variabel prediksi. Hasil penelitian memperlihatkan bahwa status fungsi ginjal pada pekerja las lebih rendah dibandingkan dengan bukan pengelas. Nikel urin merupakan variabel prediksi yang bermakna terhadap penurunan fungsi ginjal. Walaupun secara statistik diketahui bermakna, namun dalam penggunaan klinis harus dilakukan interpretasi dengan hati-hati.Kata kunci: Fungsi ginjal, nikel, pengelas, uap las